(untitled) (diségno, 2024)
The act of looking at a landscape carries with it an intention. The landscape-image has been a changing aesthetic invention. Between the 14th and 16th centuries, art moved from narrative symbolism to naturalistic iconicity, accepting landscape as a pictorial genre. With the Renaissance, an authentic landscape view began to develop through deductive reasoning and the visual experience of the image, thus surpassing the basic and flat medieval iconography. The Renaissance perspective, as a ‘symbolic form’, helped to value space as something different from the flat surface on which it is painted, although it was not the only system used to represent the three-dimensional spatiality of the scene, being one more among other possibilities. more perceptive and intuitive. This writing aims to reflect on a diachronic vision on the evolution and development of the illusory concept of distance or remoteness in the figurative representation of the landscape during its initial formulas, understood as a realistic search for the depth generated from the first terms to the backgrounds. Of the pictorial scene –whether real or imagined–. In this trajectory, the importance of the drawing treaties and manuals spread throughout Europe during the 16th and 17th centuries as recipe books or basic principles of said learning stands out. Due to its influence, it is worth highlighting Leonardo’s Trattato della Pintura as the first attempt to codify all these resources and devices ‘of illusion’, and whose validity has still remained valid in the representation of landscape to this day.